Web squared : Web 2.0 five years on - O'Reilly, Tim (O'Reilly Media, 2009)
Ever since we first introduced the term Web 2.0, people have been asking, What ™s next? Assuming that Web 2.0 was meant to be a kind of software version number (rather than a statement about the second coming of the Web after the dotcom bust), we ™re constantly asked about Web 3.0. Is it the semantic web? The sentient web? Is it the social web? The mobile web? Is it some form of virtual reality? It is all of those, and more. The Web is no longer a collection of static pages of HTML that describe something in the world. Increasingly, the Web is the world ""everything and.